PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WONDERSHARE FILMORA PADA MATA PELAJARAN TRANSMISI TENAGA LISTRIK KELAS X TJTL DI SMKN 1 PERCUT SEI TUAN - Anjas Pratama Sinaga; Baharuddin . (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract The problem in this study is that the existence of media in schools is less practical and difficult to carry and students tend to be able to because teachers explain theoretically and do not optimize technology in media. Wondershare Filmora9-based interactive learning media has never been used by teachers. The objectives of this study are (1) to determine the design process of learning media development wondershare Filmora 9 in the subject of Electric Power Transmission, (2) to determine the feasibility of learning media used in the learning process. The research model used in this study consists of Analysis, design, development, implementation, evaluation (ADDIE). The subjects of this study were students of class XI TJT SMKN 1 Percut Sei Tuan, while the validators of media assessment were UNIMED lecturers and homeroom teachers of class XI TJTL to assess the material and media. The results of this study show that interactive learning media based on Filmora 9 is classified as "Excellent". Based on the results of the assessment the validator got the category "Very Worthy" with details from the media expert validator got a percentage score of 92% with the category "Very Worthy". In the media assessment by material experts, a percentage score of 93.5% was obtained with the category "Very Worthy". Based on the four validators, it can be concluded that interactive learning media based on Filmora 9 is suitable for use for class XI students of TJTL SMKN 1 Percut Sei Tuan.Â Key Words: Media Filmora 9, feasibility, electric power transmissionÂ AbstrakPermasalahan dalam penelitian ini adalah keberadaan media di sekolah kurang praktis serta sulit untuk dibawa dan siswa cenderung bisan karena guru menjelaskan secara teoritik dan kurang mengoptimalkan teknologi dalam media. Media pembelaajran interaktif berbasis Wondershare Filmora9 belum pernah digunakan oleh guru. Tujuan penelitian ini adalah (1) untuk mengetahui proses rancangan pengembangan media pembelajaran Wondershare Filmora 9 pada mata pelajaran Transmisi Tenaga Listrik, (2) untuk mengetahui kelayakan media pembelajaran yang digunakan dalam proses pembelajaran. Adapun model penelitian yang digunakan dalam penelitian ini terdiri dari Analysis, design, development, implementation, evaluation(ADDIE). Subjek penelitian ini adalah siswa kelas XI TJT SMKN 1 Percut Sei Tuan, sedangkan validator penilaian media yaitu dosen UNIMED dan guru wali kelas XI TJTL untuk menilai materi dan media. Hasil penelitian ini menunjukkan bahwa media pembelajaran interaktif berbasis Filmora 9 tergolong pada kategori â€œSangat Baikâ€. Berdasarkan hasil dari penilaian validator mendapat kategori â€œSangat Layakâ€ dengan rincian dari validator ahli media mendapat skor persentase 92% dengan kategori â€œSangat Layakâ€. Pada penilaian media oleh ahli materi diperoleh skor persentase 93,5% dengan kategori â€œSangat Layakâ€. Berdasarkan dari keempat validator dapat disimpulkan bahwa media pembelajaran interaktif berbasis Filmora 9 layak digunakan untuk siswa kelas XI TJTL SMKN 1 Percut Sei Tuan.Â Kata Kunci: Media Filmora 9, kelayakan, transmisi tenaga listrik